Answer:
-23, [tex]y=6x-23[/tex]
Step-by-step explanation:
We need slope intercept form but do not have the needed information. We will gather this information by using point slope form. The point-slope formula is [tex]y -y_{1} =m(x -x_{1})[/tex] where we substitute a point (x,y) for [tex](x_{1},y_{1})[/tex].
We have slope represented as m=6 and (3, -5). We input m and [tex]x_{1} =3\\y_{1}=-5[/tex].
[tex]y-(-5)=6(x-3)\\y+5=6(x-3)[/tex]
We now simplify the parenthesis and solve for y to have slope intercept form.
[tex]y+5=6(x-3)\\y+5=6x-18\\y+5-5=6x-18-5\\y=6x-23[/tex]
The y-intercept is b of slope intercept form y=mx+b. Here b=-23.